Relevansi Nilai-Nilai Akhlak Dalam Bidayatul Hidayah Terhadap Hubungan Sosial Santri Di Pesantren Darul Ulum - Umam, Chairul; Usman; Sukino, Arief (Kartika: Jurnal Studi Keislaman, 2025)
This study analyzes the relevance of the moral alues of Imam Al-Ghazali proposed in Bidayatul Hidayah in view of the practice of social relations of students of Pondok Pesantren Darul Ulum, Sungai Raya, Kubu Raya. In this qualitative study case, one of the methods of the sample of ten key informants the principal (kiai), the teachers (ustadz), and the students was applied. These methods included the interviews and observation. The data was analyzed using the interactive model by Miles and Huberman, while validity was established via source and methodological triangulation. Seven principal values emerged from the findings. These values are respect and courtesy, selectivity in friendship, selflessness, trust, constructive communication, empathy, and truthfulness. These values are internalized, and learned morals are translated during the practice, daily activities, and by the teacher's role model. The principles' internalization has been instrumental in nurturing and diminished social discord. This study illustrates the character education value of classical Islamic literature in later periods of the education system, and the bedrock of turath (Islamic tradition) on character education from Islamic literature.